Origin and modifications of the geometrical centre to assess team behaviour in team sports: a systematic review. [Origen y modificaciones del punto geométrico para evaluar el comportamiento táctico colectivo en deportes de equipo: una revisión sistemática]. - Markel Rico-González; José Pino-Ortega; Fabio Yuzo Nakamura; Felipe Arruda-Moura; Asier Los Arcos (Ramón Cantó Alcaraz, 2020)
The aim of the present study was to systematically review the origin and modifications of the geometrical centre (GC) in the assessment of team behaviour in team sports. Studies were identified following the PRISMA guidelines and PICO design for systematics reviews in four electronic databases (PubMed, SPORTDiscus, ProQuest Central, and Web of Sciences). A total of 3,973 documents were initially retrieved, of which 1,779 were duplicates. After checking 2,178, another 36 were added from the references of the studies. 72 articles met de inclusion criteria and 7 were included for the systematic review. Habitually, the GC is computed as the mean [X,Y] of several or all players in the sports team. Despite the relevance of the location of the players with respect to the goal, habitually, the goalkeeper/target has not been considered in the measurement of the GC. Two techniques (i.e. Hilbert transformation and cluster analyses) have been applied to analyse the synchronisation (i.e. relative phase) and the average mutual information (AMI) to assess the complexity and regularity or predictability of the GC in team sports. Since the GC does not consider the goalkeepers and team dispersion, this measure should be interpreted with caution, but together with other tactical variables can provide interesting information for team sports technical staff.